Tenon's Patch Graft: A Review of Indications, Surgical Technique, Outcomes and Complications. (19th May 2022) - Kate, Anahita; Vyas, Sonal; Bafna, Rahul Kumar; Sharma, Namrata; Basu, Sayan
ABSTRACT: Purpose: Corneal perforations are common corneal emergencies faced by ophthalmologists across the globe. There are multiple modalities of management, most of which require an eye bank support or availability of tissue adhesives. Tenon's patch graft (TPG) is a technique that does not depend on these factors as the graft is harvested from the same eye of the patient. The aim of this review is to provide an overview of the indications, technique, normal postoperative course, and management of complications. Methods: After carrying out a literature search on "tenon's capsule", "corneal patch graft", "tenon's patch graft", "multilayered amniotic membrane" and "corneal perforations", 28 articles were included for this review. Results: TPG graft can be performed in cases of small to moderate perforations without active suppuration. The procedure can also be combined with amniotic membrane grafting or tissue adhesives to provide additional tectonic support. Postoperatively, the epithelium heals over a course 2–3 weeks and restoration of a stable ocular surface with a corneal scar is completed by the third postoperative month. Complications following the surgical procedure are rare but can include graft displacement, melt and pseudoectasia. Subsequent visual rehabilitation with contact lenses or keratoplasties can be planned in these eyes that yields good visual outcomes. Conclusions: Tenon's patch graft is a simple yet viable option in management of small to moderate corneal perforations. The procedure does not necessitate the prior availability of specialized products and can be performed with routine equipment of an ophthalmic theatre, making it an attractive option in low resource settings.